2014
DOI: 10.5455/ijmsph.2014.151020141
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of nephropathy and cardiovascular diseases in Indian patients with type 2 diabetes mellitus

Abstract: Background: It is well established that patients with type 2 diabetes mellitus are at increased risk for chronic kidney and cardiovascular diseases. Diagnosis of diabetic nephropathy and cardiovascular diseases at an early stage in patients with type 2 diabetes mellitus is difficult. Therefore, biomarker for estimation of renal function was chosen. Aims and Objectives: To evaluate serum cystatin C and its correlation with biochemical, clinical, and anthropometric parameters in patients with type 2 diabetes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Studies have demonstrated that serum cystatin C is a sensitive biomarker for detecting changes in GFR and identifying preclinical renal disease, particularly in diabetic patients with a normal serum creatinine concentration [ 9 ]. Furthermore, cystatin C is a better discriminator between type 2 diabetic patients with normoalbuminuria or microalbuminuria and its quantification is useful in the early identification of diabetic nephropathy allowing for the appropriate intervention and management [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that serum cystatin C is a sensitive biomarker for detecting changes in GFR and identifying preclinical renal disease, particularly in diabetic patients with a normal serum creatinine concentration [ 9 ]. Furthermore, cystatin C is a better discriminator between type 2 diabetic patients with normoalbuminuria or microalbuminuria and its quantification is useful in the early identification of diabetic nephropathy allowing for the appropriate intervention and management [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…One recent study Rao et al indicated that levels of cystatin C are related to subclinical renal damage and can be an earlier measurable marker of renal involvement in type 2 diabetes even before the onset of albuminuria [34]. Another study by Surendar et al found that cystatin C levels were highest in type 2 diabetic patients without microalbuminuria, indicating that cystatin C can detect early renal damage even before the development of albuminuria.…”
Section: Cystatin C As a Marker For Early Diabetic Nephropathymentioning
confidence: 99%
“…In the same context, a recent study, including 42 patients with type 2 diabetes, showed that only cystatin C level was associated with increased risk of CVD, which indicated that cystatin C may be a valuable and useful marker for predicting CVD in type 2 diabetic patients [68]. Another study also demonstrated that measurement of the levels of serum cystatin C is a useful, practical, noninvasive technique for the evaluation of renal involvement and might be related with a risk for cardiovascular events in patients without nephropathy in the course of diabetes, especially in patients with normoalbuminuria [34].…”
Section: Cystatin C As a Marker For Predicting Adverse Outcomesmentioning
confidence: 99%